MEANING OF LIFE FOR PROSTATE CANCER PATIENTS - Umi Latifah; Suwarti Suwarti (PSIMPHONI, 2022)
This research aims to describe how a person suffering from prostate cancer interprets his life and factors affecting it. The research design is a case study. The data were collected through a structured interview, passive participation observation, and documentation in the form of voice recorder or online message history. The credibility was checked through observation and triangulation. There are four steps in analyzing data: data collection, data reduction, data display, and conclusion drawing. This research involves two primary informants (prostate cancer patients), with the initials TM and MR, and three secondary informants (wives and children of the primary informants).The research result shows that self-understanding possessed by TM and MR is relatively different, in which TM is still grateful for his illness while MR is confused with the happening condition. The activities done by the informants are also different, in which one still does the activities like usual while the other reduces the activities because of the illness. MR has a relatively close relationship with his wife, in which it is contrary to the other informant. The two informants also have different responsibilities related to their illness. TM responds to his illness with a grateful feeling while MR responds to his illness with confused feelings. However,with the condition of their chronic illness, one of the informants still does not improve his relationship with God. Keyword : Prostate cancer, the meaning of life, triangulasih